Design and Analysis of R.C.C Overhead Water Tank for Town (International Journal of Innovative Research in Engineering & Management, 2022)
Storage tanks are both a common carrier and  an essential commercial establishment. The prevalent  building techniques, the physical characteristics of the  material, and the climatic circumstances all impact the  procurement and build procedures employed in steel and  concrete. Prior to beginning the design, the much more  appropriate kind of tank staging and accurate load estimate  are performed, as well as structural statically equilibrium,  particularly with regard to overturning of overhanging parts.  When the tank is full as well as empty, the design considers  the worst conceivable arrangement of stresses, moments, and  shears coming from transverse and longitudinal loads  operating in either direction. The deviation shape owing to  pressure gradient and strains, among other things, are studied  in this project by doing an Intze tank study.
Keywords: hydrostatic strain; kinds of tanks; square water tank; opinions; Meridional pressure; Hoop pressure; evaluation; layout standards as per IS code